Notes on the zoogeography of the Atlantic sea turtles of the genus Lepidochelys - Carr, Archie (Revista de Biología Tropical, 1957)
The sea turtle Lepidochelys kempi has an extensive range in coastal waters of the United States, and in parts of Florida is abundant as a seasonal resident. All known populations are sexually immature, and the breeding area of the species is not known. The present paper suggests the necessity of assuming a distant origin for the North American population, examines fragmentary evidence bearing on the corollary assumption of migratory movement, and somewhat hesitantly proposes the coast of northwestern Africa as a possible site of nesting. Spreading into American waters may occur via the Gulf Stream system. New records extend the range of the genus to northern Mauretania and into the Mediterranean.